Fabrication and in vitro evaluation of pH/thermo dual responsive hydrogels as controlled ibuprofen sodium in situ depot - Samiullah Khan; Abdur Rehman; Syed Faisal Badshah; Gamal A. Shazly; Amira Metouekel; Fakhreldeen Dabiellil (Designed Monomers and Polymers)
Ibuprofen sodium (IBP) is a commonly used NSAID for multiple pain conditions. However, despite its extensive use, it is associated with multiple GIT adverse effects after oral administration. In the present study, we have fabricated thermoresponsive gel depot using Poly (N-vinylcaprolactam) and sodium alginate as polymers. The designed formulations are intended to be used as IBP depot after being administered subcutaneously. The sol-gel phase transition temperature and gelation time of gel samples were optimized by tube inversion, rheological exploration and optical transmittances. Temperature sweep experiments confirmed that optimized gel samples have sol-gel transition between 32°C and 37°C. Swelling and in vitro drug release displayed that optimized gels have maximum swelling and IBP release at pH 7.4 and at 35°C confirming their pH/thermo sensitivity. The degradation profile of hydrogels displayed controlled degradation for 6 days that with increasing contents. MTT assay showed L929 cells displayed more than 90% cell viability against blank and IBP-loaded PNVCL/NaAlg hydrogels at optimized concentrations. Fourier transform infrared spectroscopy confirmed the polymer blend hydrogels structure formation. Thermogravimetric analysis confirmed the presence of thermoresponsive moieties and thermal stability of polymer blend hydrogel sample. While scanning electron microscopy showed that hydrogel has channels in structure that might facilitate the diffusion of solvent. Results concluded that PNVCL/NaAlg hydrogels can be utilized as IBP sustained depot following subcutaneous application invivo and GIT adverse effects could be avoided associated with its oral administration.